White Matter Integrity Is Associated With Intraindividual Variability in Neuropsychological Test Performance in Healthy Older Adults - Halliday, Drew W. R.; Gawryluk, Jodie R.; Garcia-Barrera, Mauricio A.; MacDonald, Stuart W. S. (Frontiers in Human Neuroscience, 2019)
Inconsistency of performance across neuropsychological testing instruments (dispersion) shows sensitivity to acquired injury and neurodegenerative pathology in older adults. The underlying neural correlates have remained speculative however, in spite of known white matter degradation seen in conjunction with elevated inconsistency in related operationalizations of intraindividual variability. Consistently, these operationalizations have controlled for artifactual age-related variance to increase measurement sensitivity of CNS dysfunction. In this study, dispersion was examined alongside composite scores of memory and executive functioning from the Alzheimer’s Disease Neuroimaging Initiative. 44 healthy older adults (M=72.0, SD=6.4) underwent diffusion tensor imaging and neuropsychological testing spanning a range of cognitive domains. Results replicated previous findings, demonstrating reduced microstructural integrity with advanced age and increased integrity in high memory and executive functioning performers, across all major white matter tracts. With age first regressed from the composite scores, significant associations remained between greater executive functioning scores and greater microstructural integrity in the genu of corpus callosum, anterior corona radiata bilaterally, right internal capsule and right posterior thalamic radiation. With age regressed from the dispersion scores greater values were primarily associated with decreased white matter integrity in the body and genu of corpus callosum, anterior corona radiata bilaterally and left superior longitudinal fasciculus. Dispersion is easily computed across speeded and accuracy-based measures and shows promise in detecting white matter damage, beyond that seen in the typical aging process. This appears to be the first investigation of neural correlates associated with increased dispersion.